Oxygen therapy in acute exacerbations of chronic obstructive pulmonary disease - Brill, Simon E (Int J Chron Obstruct Pulmon Dis, 2014)
Acute exacerbations of chronic obstructive pulmonary disease (COPD) are important events in the history of this debilitating lung condition. Associated health care utilization and morbidity are high, and many patients require supplemental oxygen or ventilatory support. The last 2 decades have seen a substantial increase in our understanding of the best way to manage the respiratory failure suffered by many patients during this high-risk period. This review article examines the evidence underlying supplemental oxygen therapy during exacerbations of COPD. We first discuss the epidemiology and pathophysiology of respiratory failure in COPD during exacerbations. The rationale and evidence underlying oxygen therapy, including the risks when administered inappropriately, are then discussed, along with further strategies for ventilatory support. We also review current recommendations for best practice, including methods for improving oxygen provision in the future.